Charitable activities of the military in the second half of the XIX–early XX centuries (On the materials of Western Siberia) - O. V. Gefner (Омский научный вестник: Серия "Общество. История. Современность")
Based on the analysis of unpublished sources (documentation of military institutions, public organizations) and materials of the regional periodical press, the charitable activities of the military in the cities of Western Siberia in the second half of the 19th - early 20th centuries are characterized, which, despite the great attention of the scientific community to the phenomenon of charity, did not has become the subject of special research. From the standpoint of cultural anthropology, the main directions, forms, motives of army charity are defined and characterized. The study emphasizes that the activities of the military in the field of charity are active, diverse, it is dominated by gratuitous labor and a lot of organizational work, which drew public attention to topical social problems and the development of urban culture.